Mehrdimensionale Bildung im Kontext kommunaler Bildungslandschaften : Bestandsaufnahme und Perspektiven - Berse, Christoph (Budrich UniPress, 2009)
Against the background of expanded educational ideas and the current educational discourse in Germany, the book reflects the productive approaches of multidimensional educational concepts in the redesign of municipal educational landscapes. In addition, the educational policy orientation of child and youth welfare is discussed as an ambivalent guiding norm and the various approaches in the cooperation of youth welfare and schools and all-day education are presented.